2018
DOI: 10.20448/journal.522.2018.42.85.90
|View full text |Cite
|
Sign up to set email alerts
|

Using Generalizability Theory to Assess the Score Reliability of Communication Skills of Dentistry Students

Abstract: The goal of this study is to determine the reliability of the performance points of dentistry students regarding communication skills and to examine the scoring reliability by generalizability theory in balanced random and fixed facet (mixed design) data, considering also the interactions of student, rater and duty. The study group of the research consists of the 16 dentistry students who took communication skills elective course in Hacettepe University in 2014-2015 academic year. In the study, the variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…The findings of this study are consistent with previous studies applying g-theory to examine ratings from neutral observers [ 24 , 25 ] or in other contexts [ 14 , 41 ] and are emphasized by studies investigating PPC ratings using other methods [ 18 , 42 ]. Two studies examined ratings of PCC assessed from neutral observers to evaluate students communication competence in the context of health professional training programs [ 24 , 25 ]. It was shown that students’ communication competence could only be explained to a small extent (3% [ 24 ]; 11% [ 25 ]).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The findings of this study are consistent with previous studies applying g-theory to examine ratings from neutral observers [ 24 , 25 ] or in other contexts [ 14 , 41 ] and are emphasized by studies investigating PPC ratings using other methods [ 18 , 42 ]. Two studies examined ratings of PCC assessed from neutral observers to evaluate students communication competence in the context of health professional training programs [ 24 , 25 ]. It was shown that students’ communication competence could only be explained to a small extent (3% [ 24 ]; 11% [ 25 ]).…”
Section: Discussionsupporting
confidence: 90%
“…Two studies examined ratings of PCC assessed from neutral observers to evaluate students communication competence in the context of health professional training programs [ 24 , 25 ]. It was shown that students’ communication competence could only be explained to a small extent (3% [ 24 ]; 11% [ 25 ]). This was also shown by a study examining the cultural competency of attending physicians using g-theory [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a certain number of items would be needed to obtain dependable scores. Uzun et al (2018) and de Vries (2012) also pointed out that increasing the number of raters or occasions would increase the score dependability when rater and occasion are considered as facets. Li, Shavelson, Yin and Wiley (2015)…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical communication skills are one of the competencies that must be owned by students today. Mathematical communication skills are defined as the ability to reflect an image into mathematical ideas (Nuraida & Amam, 2019;Uzun et al, 2018). Mathematical problems by using symbols and providing explanations in their own language by writing them mathematically (Al-Momany, 2015;Rahmi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%